A novel phenylsulfenylation of unsaturated acids or alcohols by methyl phenyl sulfoxide and substoichiometric (COCl)2. (22nd January 2022) - Wang, Hao; Wang, Yutong; Xiang, Fan; Wang, Yinong; Liu, Yongguo; Sun, Baoguo; Tian, Hongyu; Liang, Sen
Abstract: Phenylsulfenylation of unsaturated acids and alcohols has been achieved by methyl phenyl sulfoxide (PhSOCH3 ) and substoichiometric (COCl)2 in CH3 CN. The corresponding cyclization products, lactones with a phenylthio group from unsaturated acids were obtained in mediate to good yields, whereas the cyclic ethers with a phenylthio group from unsaturated alcohols in relatively low yields. PhSOH was proposed to be the key active species for phenylsulfenylation, which was generated in situ by the reaction of PhSOCH3 with substiochiometric amount of (COCl)2 . Anhydrous HCl could replace (COCl)2 in the reactions to give the comparable results. Graphical abstract: Image 1